Odpowiedzi

2010-01-22T22:51:39+01:00
A)(x2+2y-5x)(2x2-3y)= 2x4-3xy+4x2y-6y2-10x3+15xy= 2x4+12xy+4x2y-10x3+15xy
b)(a2-5ab+3b2)(a2-2ab)= a4-2a3b-5a3b2+3a2b2-6ab3
c) 5(x – 7y + 4) = 5x-35y+20
d) 3x(x – 9y – 11) = 3x2- 27xy-33x
e) 10ab(3,4a2b – 2,5ab – 9,3b2 – 8a2) = 34a3b2-25a2b2-93ab3-80a3b
f) 3,5x2y(6x – 8yz – y2x + 12) = 21x3y-28x2y2z-3,5x3y3+42x2y
Najlepsza Odpowiedź!
2010-01-22T23:00:06+01:00
Wykonaj mnożenia:

a)(x2+2y-5x)(2x2-3y)=2x⁴-3x²y+4yx²-6y²-10x³+15xy=
2x⁴+yx²-6y²-10x³+15xy

b)(a2-5ab+3b2)(a2-2ab)=a⁴-2a³b-5a³b+10a²b²+3a²b²-6ab³=
a⁴-7a³b+13a²b²-6ab³

c) 5(x – 7y + 4) =5x-35y+20

d) 3x(x – 9y – 11) =3x²-27xy-33x

e) 10ab(3,4a2b – 2,5ab – 9,3b2 – 8a2) =34a³b²-25a²b²-93ab³-80a³b

f) 3,5x2y(6x – 8yz – y2x + 12) =21x³y-28x²y²z-3,5x³y³+42x²y